PENGGUNAAN KONJUNGSI TOKI, TOKI(NI), TOKI (NI) WA DALAM KALIMAT BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (Universitas Diponegoro, 2015)
Conjunction toki indicates time relation that expreesses actions that occur at the same time. Toki has three variants, they are toki, toki (ni), and toki (ni) wa. Each of them has its speciality of usage. Toki is the most neutral of all. The usage of particle (-ni) and (-ni) wa affects to the usage of toki in a sentence. Toki (ni) is used to express actions that happen one time, while toki (ni) wa expresses an general actions.